Use of Proverb in Nepali Language Teaching - Bhandari, Indra Bahadur (Academia Research Journal, 2023)
Language is not only a means of human exchange of ideas, but is a gift of nature for humans only. Along with the development of language, people are advancing in the world by raising many horizons of development. The more the development of language, the more people is limiting the world within a narrow circle. Every dynamic language in the world is developing new methods and methods for its development. Similarly, among the dynamic languages, Nepali is also a dynamic and developing language. The Nepali language, developed from the Sanskrit language, has spread its influence in various countries besides Nepal. Modern linguistics recognizes language teaching as an important means of language development. Language teaching is to emphasize the specific use and development of the language while developing the listening, speaking, reading and writing of the language. Even within the same language, there are many differences, even the linguistic differences up to the language of the individual; many linguistic errors are seen in the standard use of the language. Since Nepal is a multi-lingual country, many problems have been observed in teaching language to students from different linguistic communities in the same class. It is necessary to choose appropriate linguistic materials to make language learning effective in bilingual classes. Therefore, proverbs can become very useful linguistic materials for teaching Nepali language and when using proverbs, students learn the specific use of the language on the one hand, and on the other hand, they can use the moral education given by the proverbs collected by the folk society for centuries in their daily life.